Specific patterns in correlations of super-short tandem repeats (SSTRs) with G+C content, genic and intergenic regions, and retrotransposons on all human chromosomes - Henn, Lukas; Sievers, Aaron; Hausmann, Michael; Hildenbrand, Georg Lars (Genes, 2024)
The specific characteristics of k-mer words (2 <= k <= 11) regarding genomic distribution and evolutionary conservation were recently found. Among them are, in high abundance, words with a tandem repeat structure (repeat unit length of 1 bp to 3 bp). Furthermore, there seems to be a class of extremely short tandem repeats (<= 12 bp), so far overlooked, that are non-random-distributed and, therefore, may play a crucial role in the functioning of the genome. In the following article, the positional distributions of these motifs we call super-short tandem repeats (SSTRs) were compared to other functional elements, like genes and retrotransposons. We found length- and sequence-dependent correlations between the local SSTR density and G+C content, and also between the density of SSTRs and genes, as well as correlations with retrotransposon density. In addition to many general interesting relations, we found that SINE Alu has a strong influence on the local SSTR density. Moreover, the observed connection of SSTR patterns to pseudogenes and -exons might imply a special role of SSTRs in gene expression. In summary, our findings support the idea of a special role and the functional relevance of SSTRs in the genome.
Online veröffentlicht: 25. Dezember 2023
Gesehen am 19.08.2024